How Foreign Policy Shapes American National Identity - McCARTNEY, PAUL T. (Political science quarterly, 2019)
On 22 October 2018, President Donald Trump ignited controversy when he proclaimed at a rally in Texas, "You know, they have a word-it's sort of became old-fashioned-it's called a 'nationalist.' ... You know what I am? I'm a nationalist, okay? I'm a nationalist. Nationalist. Nothing wrong. Use that word." President Trump's provocation aimed explicitly to draw a contrast with "globalism," a contrived foreign policy posture that echoes liberal internationalism. By using the word "nationalist" to implicitly reject liberal internationalism, which itself expresses deep currents in American national identity, Trump turned a discussion about America's relationship with the world into a vehicle by which to defend his vision for and understanding of the United States, one that prioritizes sharp boundaries between "Americans" and others, deemphasizes consensus building and institutionalism, and disdains foreign aid, which is often conceived as a proxy for welfare spending. Trump's invocation of nationalism, in other words, was...